Pengukuran Hasil Pendampingan Kelompok Wirausaha Baru di Kota Batu Tahun 2014 - Mohammad Zaenal Abidin; Bambang Banu Siswoyo; Wening Patmi Rahayu (University of Darussalam Gontor, 2016)
At the end of 2015, Indonesia will be entering ASEAN Economic Community. Indonesia as the largest population in South East Asia will be the largest market if the number of entrepreneur is less than standard number. Especially the competitiveness index of Indonesia comes to the 34th position in the world and in the 4th position in ASEAN. Indonesia economic growth cannot be separated from the contribution of SME. It contributes 98.7% of employment and 59,08% on gross domestic product. As contributor for Indonesia economic growth, SME also faces complex problems both internal and external. In attempt to improve quantity and quality of SME it requires well-programmed moves one of which is recent entrepreneurial assistance program organized by East Java Government. The present study aims at determining knowing mentoring component description and the effect of learning component on the success of recent entrepreneurial assistance program, the result of recent entrepreneurial assistance program, and supporting and obstacle Faktor of recent entrepreneurial assistance program in Batu.The present study employed quantitative causality associative model and embedded model of qualitative. The study consists of independent variable (X); purpose, material, instructor, media, and assistance method and dependent variable is the success of assistance program. The population of the study is the participants of entrepreneurship assistance program in Batu of 2014. The sampling technique employed is saturated sampling with 40 respondents. Analysis technique employed is multiple linear regression analysis and strengthens by the result of qualitative data analysis. The data obtained through questionnaires with Likert scale and interview.In conclusion, that the description of the mentoring program components assessed both by the participants, the size of the success of the mentoring program could be said to be good in size softskill but less good in size hardskill, the learning components; purpose, affects negatively to the success of assistance program, instructors and media affects significantly and positively to the success of assistance program, material and method do not affects significantly and positively to the assistance program. The supporting Faktor affecting the participants is faith and motivation while the obstacle Faktor is capital, tools and marketing management. The suggestions can be given is improving instructor competences and evaluating material and method of assistance program based on the needs of the participants.